Indeks Pembangunan Manusia Kabupaten Wonosobo Tahun 2014-2023 Ditinjau dari Indeks Pendidikan dan Kesehatan - Erda Dwi Cahyadi; Syafrida Reza Aulia (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
The aim of this research is to determine the human development index (HDI) in Wonosobo Regency from 2014 to 2023 based on the education index which consists of average length of schooling (ALS) and expected length of schooling (EYS) as well as health expressed by life expectancy at birth (LEB). Research data was obtained from data from the BPS-Statistic of Wonosobo Regency, Central Java Province, as well as the national BPS. The analysis in this research includes the classical assumption test, multiple linear regression analysis, coefficient of determination test, and anova test. The research results show that partially the ALS and LEB variables have a positive and significant effect on HDI, while the EYS variable has an insignificant effect. Meanwhile, the third variable has a positive and significant effect on HDI simultaneously with an influence level of 98%.